2009
DOI: 10.1002/jsfa.3480
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding intact brown seaweed Ascophyllum nodosum on some digestive parameters and on iodine content in edible tissues in pigs

Abstract: BACKGROUND: Limited research suggests that brown seaweed (extracts) may be used in pig nutrition for improving gut health and performances and for iodine enrichment of tissues. One in vitro and two in vivo experiments with dried iodine-rich intact marine seaweed (Ascophyllum nodosum) have been conducted with weaned piglets to further unravel the mechanisms. RESULTS: In vitro investigations revealed a statistically significant depressive effect of seaweed on pig gut flora, especially on Escherichia coli. In viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
75
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 63 publications
4
75
2
Order By: Relevance
“…Well-oriented villi and adjacent crypts (15)(16)(17)(18)(19)(20) were measured and the average villus length (V), crypt depth (C), V/C ratio, and total length V+C was calculated per piglet. Intraepithelial lymphocytes (IELs), expressed as IELs per 100 enterocytes, were determined according to Dierick et al (2009). This resulted in nine observations per diet group in both experiments.…”
Section: Sampling During Trial and At Slaughtermentioning
confidence: 99%
“…Well-oriented villi and adjacent crypts (15)(16)(17)(18)(19)(20) were measured and the average villus length (V), crypt depth (C), V/C ratio, and total length V+C was calculated per piglet. Intraepithelial lymphocytes (IELs), expressed as IELs per 100 enterocytes, were determined according to Dierick et al (2009). This resulted in nine observations per diet group in both experiments.…”
Section: Sampling During Trial and At Slaughtermentioning
confidence: 99%
“…However, and despite the high micromineral content of most algae species, their use as mineral supplements has hardly been studied, except for iodine (I). Seaweed supplements in livestock are considered a way to increase I content of animal products, for instance porcine meat (Dierick et al, 2009), to provide a high level of I in food I deficient areas. I excretion in milk, proportional to dietary I supplements (European Food Safety Authority (EFSA), 2005a; Flachowsky, 2007;Franke et al, 2009a) is a good way to provide I to deficient human populations.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that brown seaweeds are rich in amino acids, trace elements and vitamins; and also have antioxidant, antimicrobial and inmunomodulatory activities (Allen et al, 2001). So far, macro-algae research in animal nutrition has focused on its nutritional value and the animal performance response to dietary supplementation (Dierick et al, 2009; † E-mail: marta.miranda@usc.es Animal (2014) Rjiba et al, 2010). However, and despite the high micromineral content of most algae species, their use as mineral supplements has hardly been studied, except for iodine (I).…”
mentioning
confidence: 99%
“…Dierick et al (2009) found a significant increase in iodine content in the muscles of pigs: from 15.5 µg kg -1 in the control group to 59.5 µg kg -1 in the seaweed group (for M. psoas) and from 19.9 µg kg -1 in the control group to 55.4 µg kg -1 in the seaweed group (for M. longissimus dorsi) [4]. In the work of Svoboda et al (2009) it was also noticed that the pigs which were given selenium from Se-enriched alga (Chlorella sp.)…”
Section: The Mineral Composition Of Meatmentioning
confidence: 99%
“…They have the potential to increase animal productivity, enhance resistance against diseases, provide a better digestibility of feed ingredients, and they can improve the gut flora, thus having a positive effect on the quality of animal products [3,4]. Seaweeds have been used as feed for domestic animals for a long time, if confined to the coastal regions.…”
Section: Introductionmentioning
confidence: 99%